Glaciohydraulic supercooling - Cook, Simon J.; Knight, Peter G. (Progress in Physical Geography: Earth and Environment, 2009)
Original article can be found at: http://ppg.sagepub.com/ Copyright Sage [Full text of this article is not available in the UHRA] In this progress report we review recent work which has investigated the process of glaciohydraulic supercooling and its significance for a range of glaciological and geological phenomena. Since our last report (Knight and Cook, 2008), glaciohydraulic supercooling has been identified in new locations and under hitherto unrecognized conditions, both for modern and formerly glaciated environments. Recent work has examined the record of supercooling preserved in the landform and sediment record, within tunnel valleys and in sequences of melt-out till. We suggest that supercooling may also have important implications for glacier dynamics because of the role it may play in controlling the geometry of subglacial overdeepenings, which in turn acts as a control on the dynamics of tidewater glaciers. Despite these numerous recent scientific advances, there remains a need to critically evaluate the importance of supercooling for the various aspects of sediment entrainment and flux, glacial geomorphology and ice dynamics with which it has become associated. We illustrate how collaboration with researchers in other branches of cryospheric science, such as sea-ice scientists, might shed new light on the significance of supercooling within these various aspects of glacier science. Peer reviewed